Key competences for the development of lifelong learning in the European Union - Hozjan, Dejan [Verfasser] (My University, 2009)
"This paper discusses certain developments in education policy in the European Union since the implementation of the Lisbon strategy. Greater focus on lifelong learning as a means of increasing the competitiveness of the European Union, and establishment of several new, efficient policy tools (above all the 'open method of coordination') have, in a relatively short space of time, opened up national policies in education and training, resulting in ‘Europeanisation’ of these policies and even the beginning of a process of formation of common European core skills in education and training: a model of 'key competences' that the European citizen should possess to be able to meet the challenges of the increasingly complex environment that surrounds us." (Autorenreferat, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 2.2.5 Standards in der beruflichen Bildung; I 2.2 Europa; EU-Bildungspolitik; Lebenslanges Lernen; Schlüsselqualifikation; Kompetenzorientierung; Kompetenzprofil; Kompetenzmodell; Europäische Union